2001
DOI: 10.1177/0265407501184005
|View full text |Cite
|
Sign up to set email alerts
|

Married Couples' Conflict Responses and Marital Quality

Abstract: In order to further our understanding of conflict within a marital relationship, this study had two purposes: (i) to identify married couples' conflict response profiles, and (ii) to relate these conflict profiles to appraisals of marital quality. Spouses in 173 intact married couples completed a questionnaire that included measures of a sample of aggressive, withdrawing, and problem-solving responses occurring during conflict episodes, and indices of marital quality. Cluster analyses of married dyads' conflic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 30 publications
4
36
0
Order By: Relevance
“…Both constructive (problem-solving) and destructive (withdrawal, aggressive) tactics (Ridley, Wilhelm, & Surra, 2001;Straus & Gelles, 1986) were assessed. The specific strategies included 1) just keeping your opinions to yourself (low confrontation, destructive); 2) discussing your disagreements calmly (low confrontation, constructive); 3) arguing heatedly or shouting at each other (high confrontation, destructive); and 4) ending up hitting or throwing things at each other (high confrontation, destructive).…”
Section: Methodsmentioning
confidence: 99%
“…Both constructive (problem-solving) and destructive (withdrawal, aggressive) tactics (Ridley, Wilhelm, & Surra, 2001;Straus & Gelles, 1986) were assessed. The specific strategies included 1) just keeping your opinions to yourself (low confrontation, destructive); 2) discussing your disagreements calmly (low confrontation, constructive); 3) arguing heatedly or shouting at each other (high confrontation, destructive); and 4) ending up hitting or throwing things at each other (high confrontation, destructive).…”
Section: Methodsmentioning
confidence: 99%
“…In a similar study of married couples' conflict responses and marital satisfaction, researchers found four types of couples based on conflict style-distancing couples, engaging couples, distancing wives, and distancing husbands. Each couple type was associated with different levels of marital adjustment (Ridley, Wilhelm, & Surra, 2001). In other words, conflict style seems to be a fundamental facet of how well couples can weather the storms of marriage relationships.…”
Section: Communication and Conflict Styles In Relationshipsmentioning
confidence: 99%
“…It may be shortsighted to assume that what contributes to one partner's satisfaction contributes to the other's, especially considering the literature on gender differences in the meaning of marriage (Frank & Kupfer, ). Ridley and colleagues () found evidence of asymmetry between a number of husbands and wives in their conflict responses. Husbands and wives with asymmetric conflict responses had lower marital satisfaction than couples in which both spouses utilized positive conflict responses.…”
Section: What Do We Know About Marital Happiness?mentioning
confidence: 99%